2019
DOI: 10.3765/plsa.v4i1.4463
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous spatial information provided by dementia patients and elderly controls in narratives

Abstract: Patients diagnosed with dementia of the Alzheimer's type (DAT) often show two symptoms early on: the inability to navigate space effectively and a deterioration of their language skills, especially on semantic tasks. In this work, I look at whether the inability to navigate space is reflected in the spontaneous speech of DAT patients. Through a corpus analysis of narratives by DAT and control participants, I investigate the hypothesis that DAT patients provide less spatial information than healthy controls (mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A recent study shows that spatial preposition can reflect spatial neglect in AD patients with reduced awareness of one side of the visual field due to brain damage [37]. Prepositions such as “into” and “from” indicate directional or dynamic spatial information and can reflect deficits in spatial cognition of language [38].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study shows that spatial preposition can reflect spatial neglect in AD patients with reduced awareness of one side of the visual field due to brain damage [37]. Prepositions such as “into” and “from” indicate directional or dynamic spatial information and can reflect deficits in spatial cognition of language [38].…”
Section: Discussionmentioning
confidence: 99%
“…Preposition deficits for AD have been found in Brazilian Portuguese (Alegria et al, 2013 ). Another study—arguing that spontaneous speech mirroring the decline of effective spatial reasoning in language production—found that AD and HC used the same number of locative/stative prepositions (e.g., in, on, and at) but found significant differences for directional/dynamic prepositions (e.g., into, onto, from, and to; Bosse, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Preposition deficits for AD have been found in Brazilian Portuguese (Alegria et al, 2013). Another study-arguing that spontaneous speech mirroring the decline of effective spatial reasoning in language production-found that AD and HC used the same number of locative/stative prepositions (e.g., in, on, and at) but found significant differences for directional/dynamic prepositions (e.g., into, onto, from, and to; Bosse, 2019).…”
Section: Syntactic Featuresmentioning
confidence: 99%